Perception of voicing in English word-final consonants: examining the perceptual assimilation model - Pilus, Zahariah (Malaysian English Language Association (MELTA), 2005)
This paper presents the findings of a perception experiment that was conducted to examine the relative difficulty encountered by Malay speakers of English in contrasting voicing in word-final obstruents. The pairs of obstruents examined in the paper were /t/-/d/, /s/-/z/ and /f/-/v/. Results from the experiment are discussed in relation to the Perceptual Assimilation Model developed by Best (1994, 1995). The theory essentially claims that non-native listeners would classify foreign/ second language sounds into different categories. The relative difficulty faced by foreign or second language learners in discriminating a pair of sounds can then be predicted based on how the second language sounds are categorized. The pairs of sounds under study can be categorized as a Two Category contrast (/t/-/d/ and /f/-/v/) and a Category Goodness contrast (/s/-/z/). Because /t/-/d/ and /f/-/v/ are Two Category contrasts, it is predicted that /t/-/d/ and /f/-/v/ would be well discriminated for voicing. As a Category Goodness contrast, /s/-/z/ is predicted to be difficult to discriminate. In fact, it would be the most difficult pair to distinguish for voicing among the pairs of obstruents investigated. This paper examines whether or not the findings from the experiment fulfill the above predictions. The paper then discusses some of the implications of the findings on the model.